The PNRR project ‘DigiLetClass - Digitizing letters of Classense Library’ - Fiammetta Sabba (Bibliothecae.it, 2025)
The contribution illustrates the first findings that emerged from the analysis of the letters exchanged between Pietro Canneti (Cremona 1659 - Faenza 1730) and Mariangelo Fiacchi (Bologna 1688 - Ravenna 1777). The correspondence between them is still preserved in the Classense Library of Ravenna and has recently been transcribed and digitised as part of the DigiLetClass project (Digitizing letters of Classense Library) in order to create a digital edition open to public interest and use.